2018
DOI: 10.1016/j.vetmic.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

The nucleoside analog GS-441524 strongly inhibits feline infectious peritonitis (FIP) virus in tissue culture and experimental cat infection studies

Abstract: Feline infectious peritonitis (FIP) is a common and highly lethal coronavirus disease of domestic cats. Recent studies of diseases caused by several RNA viruses in people and other species indicate that antiviral therapy may be effective against FIP in cats. The small molecule nucleoside analog GS-441524 is a molecular precursor to a pharmacologically active nucleoside triphosphate molecule. These analogs act as an alternative substrate and RNA-chain terminator of viral RNA dependent RNA polymerase. We determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(258 citation statements)
references
References 18 publications
9
219
1
7
Order By: Relevance
“…To date, the control of FECV replication (which is the source of FIPV-causing mutant virus [45]) and the development of anti-coronavirus drugs [5,23,46] are two major preventive and therapeutic measures of FIPV. Since the coronavirus nsp5-encoded 3C-like protease (3CLpro) plays an important role in virus replication and immune evasion, 3CLpro is considered an attractive target for the development of anti-coronaviral therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the control of FECV replication (which is the source of FIPV-causing mutant virus [45]) and the development of anti-coronavirus drugs [5,23,46] are two major preventive and therapeutic measures of FIPV. Since the coronavirus nsp5-encoded 3C-like protease (3CLpro) plays an important role in virus replication and immune evasion, 3CLpro is considered an attractive target for the development of anti-coronaviral therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…[13]. While remaining a devastating disease in cat populations, recent reports describing the role of nucleoside analogs and protease inhibitors, and their potential as a treatment for FCoV infection have raised the possibility of preventing lethal FIP [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A few in vitro studies have also investigated the utility of remdesivir against non-human CoVs. For example, a study by Murphy et al reported anti-CoV activity of remdesivir's parent nucleoside, GS-441524, against an alphacoronavirus that only infects wild and domestic cats, the feline infectious peritonitis (FIP) virus (EC 50 = 0.78 μM; Table 1) [14]. In 2019, Brown et al observed some antiviral effects of remdesivir against SARS-like bat CoVs (specifically, Bat-CoV HKU3, Bat-CoV SCH014, and Bat-CoV WIV1) and MERS-like bat CoVs (specifically, Bat-CoV HKU5) [12].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Some veterinary studies have also examined the effects of the parent nucleoside, GS-441524, in cats with FIP, a condition associated with very high mortality in cats [14,16]. Gilead Sciences (Foster City, California) had provided this drug to researchers at the University of California, Davis to evaluate its potential utility in veterinary indications [35].…”
Section: In Vivo Studies: Animal Models and Veterinary Studiesmentioning
confidence: 99%
See 1 more Smart Citation